Synthesis of gamma aluminum oxide nano-powder for adsorptive removal of nitrate from aqueous solutions - Tigist Assefa Bejiga; Getasew Yehuala Gezahegn; Yosef Hagos Abrha; Amare Melaku Mengistu (Discover Materials, 2024)
Abstract Nitrate pollution of surface and groundwater could be a worldwide issue resulting in the threat to the environment and public health. The removal of nitrate from water was carried out using gamma aluminum oxide (γ-Al2O3) nano powder. The nano powder was synthesized from aluminum oxide powder using the aqueous-based reflux method and applied for nitrate removal. The surface properties of the activated γ-Al2O3 were characterized using FTIR, XRD, and BET surface area analysis. Analysis of variance (ANOVA) was used to analyze nitrate removal to determine the appropriate regression model, which was found to be the quadratic model with a coefficient of determination (R2 = 0.99). The adsorption process was observed to be dependent on initial nitrate concentration, adsorbent dose, and time. The optimized nitrate removal efficiencies were 97.01% using a dose of 2.26 gL−1, an initial nitrate concentration of 10 mgL−1, and a contact time of 45 min. Additionally, the kinetics of nitrate ion adsorption was discussed based on pseudo-first order and pseudo-second order kinetic models. The experimental data fitted well with the pseudo-second order kinetic model, indicating that the adsorption mechanism is chemisorption. The equilibrium adsorption of nitrate experimental data followed the both Freundlich and Langmuir isotherm (R2 = 0.95), implying a homogeneous nature of the γ-Al2O3 surface sites. These results suggest further consideration of the practical application of γ-Al2O3 for nitrate treatment for domestic purposes.